Influence of Diet on Endothelial Dysfunction - Lottenberg, Ana Maria; Lavrador, Maria Silvia Ferrari; Afonso, Milessa Silva [UNESP]; Machado, Roberta Marcondes (Elsevier, 2018)
Several studies have shown the role of the diet in cardiovascular diseases (CVD) as well as the action of nutrients, especially fatty acids, on endothelial dysfunction. These findings directed nutritional guidelines that prioritize the orientation of healthy dietary patterns, which are associated with lower cardiovascular risk. The influence of the diet on several stages of atherosclerosis development has already been demonstrated, such LDL-c particles retention followed by the recruitment of immune cells into the subendothelial space, interaction among endothelial cells, platelets, and smooth muscle cells, and alteration of endothelial function. This chapter aims to discuss the action of micronutrients and macronutrients on lipid metabolism, inflammatory processes and on innate and adaptive immune responses, all of which are closely related to the genesis of endothelial dysfunction.
Keywords: Cardiovascular disease; Cholesterol; Diet; Endothelial dysfunction; Fatty acids; Lipids; Micronutrients